The Historical and Theoretical Rationale for Ecological Protection and Restoration: Experiences from China - Xiaotong Han; Zhengfu Bian; Haochen Yu; Shaogang Lei; Yibo Zhao; Yingjie Guo (Land)
This study aims to elucidate the historical justification for protection and restoration efforts in China while also examining the theoretical underpinnings of ecological conservation and restoration. Utilizing a literature review method, logical reasoning method, and inductive summarizing method, the historical and theoretical frameworks of territorial spatial ecological conservation and restoration are elucidated, leading to the following conclusions: (1) The ecological protection and restoration of national land space represents an advanced form of land remediation; however, they differ in terms of objects, principles, goals, and measures. (2) Territorial space ecological protection and restoration is historically unavoidable due to the current phase of societal development, driven by the natural environment and the necessity to establish an ecological civilization. (3) To implement territorial spatial ecological protection and restoration effectively and rationally, it is essential to comprehend its systematicity, territoriality, dynamics, and scientificity. By clarifying its historical and theoretical rationale, we can achieve a deeper understanding of its current relevance. This can effectively inform practical efforts in territorial spatial ecological protection and restoration.